#103 Comparative studies of analytical methods for simultaneous estimation of antibacterial agents in bulk and parenteral preparation - Moon, Shruti (Journal of Pharmaceutical Chemistry, 2022)
To determine the comparative studies of analytical methods for simultaneous estimation of drug Meropenem and Sulbactam sodium in bulk and parenteral preparation. Literature survey reveals that techniques have been developed to estimate Meropenem and Sulbactam sodium individually. No method has been reported to evaluate Meropenem and Sulbactam sodium in combined form. Hence the above combination is selected. In the RP-HPLC process, the analyte resolved using 3.2 g of tetra heptyl ammonium bromide in a 1000 mL volumetric flask then add 400 mL acetonitrile with 44 mL of buffer solution at pH 7.0 and 4 mL of buffer solution at pH 4.0 dilute it to 1000 mL with distilled water at a flow rate of 0.6 mL/min on a gradient HPLC system containing UV-visible detector and Intersil C18 column. The detection was achieved at 230 nm. The method gives better resolution with a suitable retention time. In this method, drug determined by using a mobile phase which is ethanol: water: acetic acid (5:2:3 v/v/v) composition in TLC plate with the help of an automatic sample applicator, the plate which used was chromatographed in twin through glass chamber saturated in the mobile phase for 30 min. After a chromatographic development method, the plate was removed and air-dried. After that, separated bands on the TLC plate were scanned with the help of a wavelength range of 200-700 nm. The wavelength 230 nm had suggested for the densitometric evaluation of the separated bands, and detection was achieved at 230 nm. All strategies were confirmed in terms of accuracy and range in an analysis. The system is reliable, reproducible, selective, sensitive, rapid, economic. These analytical methods are applicable for evaluating these drugs in quality control laboratories. These methods can be suggested to estimate Meropenem and Sulbactam sodium in biological fluids.
Keywords: aaa